Wine Lees as a Source of Antioxidant Compounds - María José Jara-Palacios (MDPI AG, 2019)
The winemaking industry produces large amount of byproducts, including grape pomace, stalks, and lees. Wine lees are a natural source of phenolic compounds, which have important antioxidant and biological properties. Due to the high quantities produced worldwide, this byproduct can be an ideal raw material for obtaining phenolic compounds that could be of interest in the food and pharmaceutical industries. In this mini review, the main characteristics of wine lees as well as their phenolic composition and antioxidant activity have been summarized from the information in the literature.